Federico d'Aragona (1451-1504): Politica e ideologia nella dinastia aragonese di Napoli - Alessio Russo (Regna: Testi e studi su istituzioni, cultura e memoria del Mezzogiorno medievale, 2018)
The complex life of Frederick of Aragon, second-born of Ferdinando I of Naples, is analyzed through a work of decomposition and interpretation of the data that concern to the political, cultural and ideological physiognomy of a character considered marginal in the the dramatic Italian events of the end of the XV century. Frederick represents instead, in his formation and his roles, the extraordinary experiment that was the Aragonese system of government, and the meaning of a whole political civilization: the Renaissance of the specula principis, of the political art, that can show once more the measure of its inexhaustible originality through the reconstruction of lives as this, transversals, uniques and deeply absorbed in the practice of the power.